Determination of safe vehicle speeds on wet horizontal pavement curves. Issue 11 (2nd November 2021) - Peng, J.; Chu, L.; Fwa, T. F.
Abstract : Knowing the maximum safe driving speed on a pavement curve under wet condition is crucial in achieving safe driving in wet weather. This information is valuable for pavement engineers in paving materials selection, mix design, drainage design and pavement maintenance treatment design to meet the skid resistance requirements for the safe driving speed. Unfortunately, due to the complex variables involved (including pavement surface material properties, tire properties and water film thickness), currently there is no practical working procedure that allows pavement engineers to determine the maximum safe driving speed of a vehicle on a horizontal curve under wet weather condition. To bridge this gap, this paper presents a finite element simulation model that predicts the maximum safe driving speed for a vehicle on a horizontal pavement curve (with known pavement material properties) in wet weather when there is a layer of water on the pavement surface. The maximum safe driving speed was derived by first calculating the available tire–pavement frictional resistance using the finite element simulation model, followed by a tire skidding potential analysis considering the available tire–pavement frictional resistance and the centrifugal force acting on the tires. The development and validation of the simulation model are described in this paper, and numerical examples are presented to illustrate its application in the determination of maximum safe vehicle speed. The procedure and input data (including pavement material properties and drainage data) required for calculating the maximum safe vehicle speeds on actual in-service pavement curves are presented and explained. GRAPHICAL ABSTRACT: UF0001